Perlindungan Hukum Terhadap Masyarakat Adat dalam Pemberian Izin Penugasan Survey Pendahuluan dan Eksplorasi Panas Bumi - Lating, Muhaimin Qadri; Mustamu, Julista; Holle, Erick Stenly (CAPITAN: Constitutional Law & Administrative Law Review, 2025)
The issuance of Preliminary Survey and Exploration Assignment (PSPE) permits for geothermal energy often triggers agrarian conflicts with indigenous communities, as seen in the case of Wapsalit Village, Lolong Guba District, Buru Regency. This study analyzes the validity of the PSPE permit granted to PT. Ormat Geothermal Indonesia (PT. OGI) and its legal implications for the rights of indigenous communities. The research employs a juridical-normative legal method. The findings indicate that the issued PSPE permit is not entirely valid procedurally and neglects the rights of indigenous communities. PT. OGI failed to resolve land use issues in accordance with applicable regulations and did not adequately involve the community in socialization efforts. Consequently, the constitutional rights of indigenous communities over their territories were violated, and PT. OGI may be subject to administrative sanctions. The implementation of the Free, Prior, and Informed Consent (FPIC) principle, along with enhanced supervision and sanctions for violators, is essential to ensuring more effective legal protection for indigenous communities.